Demographic Transitions in East Asia: Cultural Contexts, Contemporary Problems, and Strategic Solutions - Kurmi, Balawant (Butwal Campus Journal, 2025)
This study examines the demographic transitions in East Asia, focusing on the dual challenges of ultra-low fertility and rapid population aging. It aims to analyze the cultural, historical, and socioeconomic factors underpinning these shifts and evaluate policy responses to address them.A qualitative research approach was employed, synthesizing secondary data from demographic reports, policy documents, and scholarly literature. Case studies from China, Japan, and South Korea were used to illustrate how Confucian traditions, state interventions, and modernization processes have shaped fertility and aging patterns. Comparative analysis was conducted to highlight similarities and divergences in policy strategies across the region. Findings indicate that persistent Confucian cultural norms—particularly gendered family roles and strong filial obligations—interact with economic pressures such as high housing, education, and childcare costs to reinforce ultra-low fertility trends. At the same time, healthcare advancements and historical baby booms have fueled unprecedented population aging. Policy measures, including pronatalist incentives, workplace reforms, eldercare programs, and technological innovations, demonstrate mixed effectiveness. Monetary incentives alone have proven insufficient; structural barriers in gender equity, labor practices, and cultural expectations remain central obstacles. The rapid aging of rural populations and rising dependency ratios further underscore the urgency of integrated social and economic reforms. East Asia’s demographic trajectory reflects both resilience and vulnerability. The region’s experience illustrates that sustainable demographic strategies require comprehensive, multidimensional approaches—combining financial support, cultural adaptation, and institutional innovation. As the first region to face extreme aging alongside persistent low fertility, East Asia provides vital lessons for global population policy and long-term social sustainability.